The political economy of food price policy in Egypt - Ahmed Farouk Ghoneim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The study focuses on the period 2004-09 during which Egypt experienced food crisis. The political economy context on how the government responded to the crisis is analysed while pinpointing to what extent there was a pass-through effect from international to domestic prices. The complexity of food price policy issues and their entanglement with poverty, agricultural, and economic policies in Egypt together with the structural aspects of the food subsidy policies are discussed and evaluated from a political economy perspective. Prospects for reform or lack thereof are also analysed in the context of the 25 January 2011 revolution and new political set-up.
Keywords: H12; I38; P48; Q18; 330; food price policy; political economy; efficiency of subsidies; food crisis; Egypt; Ernährungssicherung; Ernährungspolitik; Lebensmittelpreis; Ägypten